Peran Budaya Organisasi Dalam Meningkatkan Komitmen Organisasi Pegawai CV Rumah Mesin - Muhammad Ihza Rey; Ayub Ilfandy Imran (Journal of Communication, Business and Social Science (JCOBS), 2024)
Every organization certainly has its own culture that is embraced by all members of the organization, as well as agenciesand companies. The organizational culture plays a role in many aspects of organizational life. An example of this aspectis organizational commitment, so that this research was created which aims to determine the role of organizational culturein increasing organizational commitment with the subject of research, namely CV Rumah Mesin. In this study a qualitativeapproach was used with a narrative descriptive method to find research results in the form of facts and are realistic. Basedon this approach, the data in this study were obtained from interviews with one key informant and two supporting informants.The data obtained is written narratively, namely by describing the results of the research in the form of descriptive words,not numbers. The boundaries of the topic of organizational culture and organizational commitment examined in this studyare elements of organizational culture and components of organizational commitment. This research concludes that theelements in organizational culture have a role in increasing the commitment of members of an organization in terms ofloyalty and increasing performance in carrying out their duties as members of an organization.